Mimicking pregnancy as a strategy for breast cancer prevention. (July 2013) - Santucci-Pereira, Julia; George, Christina; Armiss, David; Russo, Irma H; Vanegas, Johana E; Sheriff, Fathima; de Cicco, Ricardo Lopez; Su, Yanrong; Russo, Patricia A; Bidinotto, Lucas T; Russo, Jose
SUMMARY Pregnancy and its effects on breast cancer risk have been widely investigated; there is consensus among researchers that early pregnancy confers protection against breast cancer later in life, whereas nulliparity and late-age parity have been associated with increased risk of developing breast cancer. The answer to the question of how pregnancy reduces breast cancer risk has been elusive; however, pregnancy, like breast cancer, is a similar hormone-dependent entity under direct control of estrogen, progesterone and, of particular importance, human chorionic gonadotropin (hCG). In this report, we emphasize the main changes, previously described by our laboratory, in morphology and gene expression levels of the mammary gland of Sprague–Dawley rats exposed to known cancer-preventative conditions (pregnancy, hCG and progesterone + estrogen). In addition, we postulate a protective mechanism induced by hCG that could reduce the cell's potential to be transformed by carcinogens.